Unpublished Cuneiform texts from Tell Abu Inteek (Journal of the College of Education for Women, 2019)
Produced ancient Iraqi civilization among the ingredients of civilization as a result ofhuman interaction with the environment in which they live , and began this ingredient in asimple and took vary and evolve with the evolution of human life itself.And passing epoch long time occupied by this civilization in the land of Mesopotamia,which reflected the legibility Althelol archaeological scattered in most parts of this landemerged features of this civilization has been able shovels prospectors that secreted into theessence of knowledge to the archaeological researcher and specialist process of analysis andextrapolation of all information contained and provided by the missions excavation whichbegan in archaeological excavations in Tlul many in Mesopotamia